2020
DOI: 10.3928/1081597x-20200616-01
|View full text |Cite
|
Sign up to set email alerts
|

Comparison Between Bilateral Implantation of a Trifocal IOL and Mix-and-Match Implantation of a Bifocal IOL and an Extended Depth of Focus IOL

Abstract: PURPOSE: To compare the clinical outcomes of mix-and-match implantation of a diffractive extended depth of focus intraocular lens (IOL) (TECNIS Symfony ZXR00; Johnson & Johnson Vision) and a diffractive bifocal IOL (TECNIS ZLB00 +3.25 diopters [D]; Johnson & Johnson Vision) and bilateral implantation of a diffractive trifocal IOL (AcrySof IQ PanOptix; Alcon Laboratories, Inc). METHODS: This prospective comparative study compares the clinical out… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
28
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
7

Relationship

2
5

Authors

Journals

citations
Cited by 25 publications
(29 citation statements)
references
References 30 publications
1
28
0
Order By: Relevance
“…Recently, the blended implantation strategy has been attempted to take advantage of the merits of both IOL types, and good results have been reported [ 13 , 23 , 24 ]. In a previous study, we compared the visual performance of patients with mix-and-match implantation of an EDoF IOL in the dominant eye and a bifocal IOL in the nondominant eye with trifocal IOL implantation in both the eyes [ 17 ]. According to this study, patients with the mix-and-match implantation showed better visual acuity results from the far to intermediate distance, while patients with the trifocal IOL achieved better visual acuity results at the near distance.…”
Section: Discussionmentioning
confidence: 99%
See 3 more Smart Citations
“…Recently, the blended implantation strategy has been attempted to take advantage of the merits of both IOL types, and good results have been reported [ 13 , 23 , 24 ]. In a previous study, we compared the visual performance of patients with mix-and-match implantation of an EDoF IOL in the dominant eye and a bifocal IOL in the nondominant eye with trifocal IOL implantation in both the eyes [ 17 ]. According to this study, patients with the mix-and-match implantation showed better visual acuity results from the far to intermediate distance, while patients with the trifocal IOL achieved better visual acuity results at the near distance.…”
Section: Discussionmentioning
confidence: 99%
“…All patients were 21 years or older at the time of enrollment and underwent surgery of the second eye within seven days after surgery of the first eye. e exclusion criteria were the same as previous studies [17].…”
Section: Methodsmentioning
confidence: 99%
See 2 more Smart Citations
“…Trifocal IOLs can provide good functional results for far, near and intermediate distances. 6 , 7 , 54 They are superior to monofocal IOLs at near and intermediate distance and provide better optical quality than bifocal IOLs at intermediate distance. 8 , 9 It has also been demonstrated that trifocal IOLs improve the near and intermediate reading acuity.…”
Section: Discussionmentioning
confidence: 99%